Penyuluhan Gizi Seimbang pada Balita di Rumah Sakit Mitra Medika Tanjung Mulia - Chintami Octavia; Eric Winarno (Lembaga Pengembangan Kinerja Dosen, 2025)
The nutritional status of toddlers significantly influences their growth and development, especially during the first five years of life. PSG 2017 data indicates that the prevalence of stunting in toddlers is 27.5%, underweight 8.0%, severely underweight 3.1%, malnutrition 22.8%, and overnutrition 17.8%. If left unaddressed, nutritional problems can lead to growth disorders, increased susceptibility to illness, and physical, psychomotor, and mental development delays.Higher education institutions play a role in community service, such as providing nutrition education for mothers of toddlers at Mitra Medika Tanjung Mulia Hospital. This activity was conducted in collaboration with Posyandu at RT 17, Kendang Mas Village, including toddler weight monitoring and education for health cadres and parents. Among 15 participating toddlers, 8 (53%) had good nutrition, 4 (26%) were undernourished, and 3 (21%) were overnourished. Counseling through lectures and leaflets effectively improved mothers’ knowledge of balanced nutrition and food preparation.